2008
DOI: 10.1017/s1368980007000274
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the prevalence of anaemia in Japanese adult women, 1989–2003

Abstract: Objective: There is an increasing concern of anaemia in Japanese women, but no national trend data has existed to date. We analysed long-term national trends of anaemia in adult women. Design: Secondary analyses of 15 consecutive cross-sectional nationwide surveys conducted during the period 1989-2003. Analyses were based on 5-year intervals (1989-1993, 1994-1998, 1999-2003). Setting: Japan. Subjects: The subjects included the National Health and Nutrition Survey of Japan (NHNS-J) population. Analyses were bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 14 publications
2
16
1
Order By: Relevance
“…To our knowledge, this study is the first nationally representative cross-sectional study to evaluate the trends in nutritional status of community-dwelling elderly people [6,7,11]. In the current study, similar prevalence of anemia was observed in men (19.3%) and women (21.7%) compared to other developed countries.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…To our knowledge, this study is the first nationally representative cross-sectional study to evaluate the trends in nutritional status of community-dwelling elderly people [6,7,11]. In the current study, similar prevalence of anemia was observed in men (19.3%) and women (21.7%) compared to other developed countries.…”
Section: Discussionsupporting
confidence: 67%
“…In this project, the government set goals to increase the proportion of elderly who are physically active, i.e., those with exercise habits. This health policy may have contributed to improving general health in the elderly, resulting in increase in subjects with exercise habits and decrease in anemia (Table 1), reversing previous trends [7]. Further monitoring of the health status of community dwelling elderly should be conducted, in order to investigate the effect of national health policies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the prevalence of low Hb values is more than 5% in the population, it is regarded as a public health problem (26). On the basis of Hb concentrations, the WHO established the following criteria for assessing the public health significance of anemia: if its prevalence in the general population is 5-19.9% -low; 20-39.9% -moderate; and ≥40% -severe (1,5,8). Due to the varying distribution of social and biological risk factors for anemia and the fact that it can lead to medical, social and economic consequences, epidemiological studies of anemia are becoming increasingly important (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Average age of anemic men was significantly higher compared with healthy men, as opposed to average age of anemic women, which was significantly lower than average age of healthy women (p<0.05). It has been shown that in men Hb levels decrease with age, while in women they increase after the menopause up to the age of 70, thereafter gradually decreasing (8,22,28,31). While some authors explain it with the decreased erythroid capacity of the bone marrow (31), others point out that anemia should not be considered a normal consequence of ageing (12,19,24).…”
Section: Discussionmentioning
confidence: 99%